PENGARUH PENERAPAN PROJECT-BASED LEARNING DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATA KULIAH AKUNTANSI PENDIDIKAN - Fatmawaty Damiti; Rierind Koniyo (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT Improving the quality of higher education requires learning strategies that actively engage students while fostering independent learning as a key determinant of academic success. Although Project-Based Learning (PjBL) has been widely implemented in higher education, empirical evidence regarding its combined effect with learning independence on student learning outcomes in Educational Accounting courses remains limited. Therefore, this study aimed to analyze the influence of Project-Based Learning and learning independence on students’ learning outcomes in the Educational Accounting course at the Department of Economic Education, Faculty of Economics and Business, Universitas Negeri Gorontalo. This study employed a quantitative approach using a correlational research design. The sample consisted of 62 fifth-semester students selected through purposive sampling. Data were collected using questionnaires, interviews, observations, and documentation, and were analyzed using multiple linear regression after satisfying the classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. The findings revealed that Project-Based Learning had a positive and significant effect on students’ learning outcomes. Learning independence also exerted a positive and significant effect, with a greater contribution than Project-Based Learning. Simultaneously, both variables significantly influenced learning outcomes, explaining 56.70% of the variance. These findings suggest that integrating Project-Based Learning with the enhancement of learning independence provides an effective instructional strategy for improving students’ academic achievement in Educational Accounting courses and offers practical implications for strengthening student-centered learning practices in higher education. ABSTRAK Peningkatan kualitas pembelajaran di perguruan tinggi memerlukan penerapan strategi yang mampu mendorong keterlibatan aktif mahasiswa sekaligus memperkuat kemandirian belajar sebagai faktor pendukung keberhasilan akademik. Penelitian ini bertujuan menganalisis pengaruh Project-Based Learning dan kemandirian belajar terhadap hasil belajar mahasiswa pada mata kuliah Akuntansi Pendidikan di Jurusan Pendidikan Ekonomi, Fakultas Ekonomi dan Bisnis, Universitas Negeri Gorontalo. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Sampel penelitian berjumlah 62 mahasiswa semester V yang dipilih melalui teknik purposive sampling. Data dikumpulkan menggunakan kuesioner, dokumentasi, observasi, dan wawancara, kemudian dianalisis dengan regresi linier berganda setelah memenuhi uji asumsi klasik yang meliputi normalitas, multikolinearitas, dan heteroskedastisitas. Hasil penelitian menunjukkan bahwa Project-Based Learning berpengaruh positif dan signifikan terhadap hasil belajar mahasiswa. Kemandirian belajar juga berpengaruh positif dan signifikan, dengan kontribusi yang lebih besar dibandingkan variabel Project-Based Learning. Secara simultan, kedua variabel memberikan pengaruh positif dan signifikan terhadap hasil belajar dengan kemampuan menjelaskan variasi hasil belajar sebesar 56,70%. Temuan ini menunjukkan bahwa pengintegrasian pembelajaran berbasis proyek dengan penguatan kemandirian belajar dapat menjadi strategi yang efektif dalam meningkatkan kualitas pembelajaran dan pencapaian akademik mahasiswa pada mata kuliah Akuntansi Pendidikan di perguruan tinggi.